Knowledge discovery of Middle East dust sources using Apriori spatial data mining algorithm - Papi, Ramin; Attarchi, Sara; Darvishi Boloorani, Ali; Neysani Samany, Najmeh (Ecological informatics, 2022)
Identifying the areas susceptible to dust storm formation is one effective way of dealing with this destructive environmental phenomenon. This study is the first attempt to employ the Apriori spatial data mining algorithm to dust source susceptibility mapping (DSSM). The research process was based on extracting association rules between spatial-temporal patterns of dust drivers (including soil, vegetation, and climate parameters) in the Middle East's hotspots dust sources (HDSs). For this purpose, HDSs were identified using visual interpretation of sub-daily MODIS-Terra/Aqua RGB images from 2000 to 2021. The Middle East's HDSs mainly correspond to desert areas with poor vegetation cover and ephemeral/dried-up water bodies. A total of three million rules were extracted by running the Apriori algorithm. Accordingly, bare and non-vegetated lands, high soil thickness, low soil moisture, very high wind speed, and high temperature were identified as the most common features of HDSs. Using three measures including support, confidence, and lift, 54 frequent, reliable, and logical rules were selected, and the related maps were generated. Then, the susceptible dust sources (SDSs) map of the Middle East was produced in five classes of extreme (13% of the areas), high (14%), moderate (16%), low (17%), and no (40%) susceptibility through the weighted linear combination of the rule maps. The accuracy of the identified SDSs was estimated at 83.7% using the verification points. A sensitivity analysis was performed using the leave-one-out method to determine the isolated effect of the selected rules on the produced SDSs map. The model uncertainty varied between 15.7% and 16.8% for different rules. The variation range of uncertainty was 1.1%, demonstrating that a single rule does not significantly affect the model's performance; however, some rules have a more influential role. Our results revealed that Apriori's ability to provide generalizable association rules is a robust algorithm for DSSM. [Display omitted] •The Apriori algorithm can efficiently identify susceptible dust sources.•Association rules of dust drivers and hotspots are extracted.•Susceptible dust sources in the Middle East are identified with an accuracy of 83.7%.•Non-vegetated areas are the most frequent element in all association rules.•According to sensitivity analysis, uncertainty changes in the rules vary by up to 1.1%.